Effects and safety of Ginkgo biloba on blood metabolism in type 2 diabetes mellitus: a systematic review and meta-analysis - Zou, Huimin; Fang, Jingxian; Han, Yu; Hu, Xue; Meng, Jian; Huang, Fang; Xu, Hui; Lu, Chengfei; Wang, Yiwen; Zhang, Lili; Dong, Xiaohong; Yu, Yanmei; et al. (Frontiers in Endocrinology, 2024)
Background There has existed controversy regarding the use of Ginkgo biloba (GKB) for blood metabolism among type 2 diabetes mellitus(T2DM) patients, and we tried to analyze the effects and safety of GKB on T2DM patients. Methods We conducted a literature search between January 2003 and December 2022 of seven online databases (PubMed, Scopus, Embase, Google Scholar, Web of Sciences, Cochrane Library, and China National Knowledge Infrastructure). A systematic literature review and meta-analysis were performed to compare the effects and safety of GKB among T2DM patients. Four groups of parameters were extracted and analyzed: hemorheology parameters, lipid profile, glycemic control markers, and adverse events. Results In the end, 13 eligible articles with 11 indicators among 1573 patients were included. In the hemorheology parameters section, GKB showed significantly lower plasma viscosity (PV) (SMD=-0.91, 95%CI [-1.45, -0.36], P<0.01) and hematocrit (Hct) (SMD=-0.60, 95%CI [-0.97, -0.24], P<0.01) than the control group. GKB shoed higher velocity of the dorsalis pedis artery (VDPA) (SMD=0.51, 95%CI [0.26, 0.76], P<0.01) and ankle brachial index (ABI) (SMD=0.71, 95%CI [0.32, 1.10], P<0.01) than the control. In both the lipid profile and glycemic control markers sections, we did not find any difference between GKB and control groups, including total cholesterol (TC), triglyceride (TG), low-density lipoprotein (LDL), high-density lipoprotein (HDL), hemoglobin A1c (HbA1c), and fasting serum glucose (FSG). In addition, we saw no difference in adverse events (AE). The sensitivity analysis and funnel plot showed that the results in this research were robust and had no publication bias. Conclusion In conclusion, GKB might safely reduce the risk of peripheral arterial or even systemic cardiovascular disease. However, GKB did not directly improve lipid and blood glucose levels in T2DM patients. Systematic review registration https://inplasy.com/, identifier INPLASY202350096.